BENEFITS OF ALOE VERA SUBTANCE AS ANTI-INFLAMMATORY OF STOMATITIS - Chindo, Nycho Alva (Majority, 2015)
Nycho Alva Chindo Faculty of Medicine, Lampung University Abstract Inflammation of stomatitis often occurs as yellowish white spots with slightly concave and reddish halo, and painful. The treatment of stomatitis inflammation is basically to suppress the inflammation, reduce the pain and to increase the healing process. Some studies suggest that Aloe Vera is one of the herbs that can be processed into herbal medicine. Aloe Vera contains a variety of anti-inflammatory agents such as salicylic acid, ndometasin, mannose-6-phosphate, B-sitosterol, are also components of lignin, saponins and anthaquinone consisting of aloin, barbaloin, anhtranol, anthracene, aloetic acid, aloe emodin is basic ingredients of drugs that act as antibiotics and painkillers. In addition, that contained indomethacin can reduce edema, inhibit cyclooxygenase enzymes and inhibit the motility of poly morpho nuclear leukocytes (PMN) which when excessive amounts can damage tissue. So it can be concluded that the content of chemical compounds in Aloe Vera contains many benefits, especially as anti-inflammatory agents. Keywords: anti-inflammatory, poly morpho nuclear Abstrak Stomatitis terjadi biasanya berupa bercak putih kekuningan dengan permukaan agak cekung dan dikelilingi tepi kemerahan, serta sakit. Terapi radang mukosa mulut pada dasarnya ditujukan untuk menekan peradangan, mengurangi rasa perih dan mempercepat penyembuhan. Beberapa penelitian mengatakan bahwa Aloe Vera merupakan salah satu tumbuhan berkhasiat yang dapat diolah menjadi obat herbal. Lidah buaya mengandung berbagai agen anti inflamasi seperti asam salisilat, indometasin, manosa-6-fosfat, B-sitosterol, juga komponen lignin, saponin dan anthaquinone yang terdiri atas aloin, barbaloin, anhtranol, anthracene, aloetic acid, aloe emodin merupakan bahan dasar obat yang bersifat sebagai antibiotik dan penghilang rasa sakit. Selain itu, terdapat indometasin yang dapat mengurangi edema, menghambat enzim siklooksigenase dan menghambat motilitas dari leukosit poly morpho nuclear (PMN) yang bila jumlahnya berlebihan dapat merusak jaringan. Sehingga dapat ditarik kesimpulan bahwa kandungan senyawa kimia pada Aloe Vera mengandung banyak manfaat terutama sebagai zat anti inflamasi. Kata kunci: anti inflamsi, poly morpho nuclear